Between-group variation in Enchenopa treehopper juvenile signaling (Hemiptera Membracidae). Issue 3 (4th May 2018) - Rodríguez, Rafael L.; Wojcinski, Joseph E.; Maliszewski, Jak
Abstract : Social plasticity may be an important originator of divergence in mating signals and other sexual traits. Understanding the evolutionary causes and consequences of social plasticity requires analyzing how different features of the social environment influence the expression of signals and preferences. Here we focus on experience of signaling environments. We adopt the vantage point of a hypothetical focal juvenile individual, and ask whether its experience of the interactions between other individuals in the group would vary across groups of different size and species composition. We worked with Enchenopa treehoppers, group-living herbivorous insects that communicate with plant-borne vibrational signals as juveniles and adults. We manipulated group composition and size experimentally and monitored the behavior of the juvenile treehoppers. We found that the treehoppers' signaling rates varied with group type, size, and disturbance. Although our results likely underestimate the range of variation in behavior across groups of juveniles, they suggest that variation in the experience of signaling environments during juvenile development has the potential to contribute to social plasticity in the mating signals and mate preferences.